The validation of a screening tool for the identification of dysphagia in the paediatric population with HIV/AIDS - Vermeulen, Suzanne (Division of Communication Sciences and Disorders, 2015)
Background: The paediatric population with HIV is at higher risk for feeding and swallowing difficulties (FSD) than the general paediatric population, which may contribute to increased morbidity and mortality. Consequences of dysphagia may include insufficient nutritional intake leading to growth faltering, decreased quality of life, and risk of aspiration which may cause respiratory complications and permanent lung damage. Currently, no validated screening measures exist for the identification of FSD in infants and children with HIV/AIDS. Early identification and appropriate management of dysphagia is essential to prevent further complications and negative health outcomes. Research Aims: To determine the validity and reliability of a caregiver questionnaire as a FSD screening tool in infants and children with HIV/AIDS. As a sub-aim, the nature of FSD and the relationship between FSD and other factors, such as age, lower respiratory tract infection, undernutrition and HIV-related factors were also described. Method: A prospective, descriptive clinimetric research design was utilised. Three experts in the field of paediatric FSD were consulted to determine face and content validity of the tool. Key informant interviews were conducted with 15 caregivers of children with HIV, to determine the linguistic appropriates of the tool. Sixty-six participants with HIV/AIDS under the age of 13 years were recruited from the Infectious Diseases Clinic at Red Cross War Memorial Children's Hospital. The screening tool and a comprehensive feeding and swallowing evaluation were conducted with all participants. Additional medical information, such as HIV data, anthropometry information and history of respiratory illness were recorded. Results: The screening tool - the Feeding and Swallowing Questionnaire - was found to have face and content validity. Criterion validity was established with sensitivity of 92% and specificity of 59%. The tool has high internal consistency (Cronbach's alpha = 0.78) and excellent inter-rater reliability (100% agreement). Twenty-five (38%; N=66) participants presented with FSD. Difficulties were noted in all phases of swallowing, as well as behavioural feeding difficulties and delays in reaching age-appropriate feeding and swallowing milestones. FSD were significantly inversely associated with age (p =.008) and length of time on antiretroviral therapy (p =.014) i.e. younger children and children on ART for a short period of time were most likely to have FSD. Conclusions: The results confirm that the Feeding and Swallowing Questionnaire is a reliable and valid tool for the identification of FSD in infants and children with HIV. This tool identifies children likely to have FSD, thereby indicating referral for comprehensive assessment of feeding and swallowing, as well as the necessary management of any FSD. The results highlight the multifaceted nature of FSD in this population. Early identification of FSD may not only benefit the child, but may decrease the associated social and economic burden of frequent hospitalisation related to FSD.